MANAGEMENT TEAMS - S. Нorbachenko; V. Kharlamova (Ринкова економіка: сучасна теорія і практика управління, 2019)
The peculiarities of the creation of management teams in Ukraine at the present stage of the information society to solve the tasks are investigated. As technology evolves, so does the responsibility of people for their work, and so for the sake of simplification and productivity of the team began to appear in large organizations groups of people who share responsibilities. The method of solving problems with the help of “team thinking” significantly improves the work of the organization, such indicators as the number of ideas, creative approach to solving problems and teaming. The actual problems of the formation of separate direction in management are analyzed and ways of effective functioning of management teams are suggested. The article examines the modern experience of approaches to team management.